NBC 3171: A recarved Old Babylonian-Kassite seal - Lassen, Agnete W.; Jiménez, Enrique (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2022)
In 1960, Buchanan published a selection of cylinder seals held by the Yale Babylonian Collection. His catalogue lists NBC 3171 as no. 90 under the heading ‘Early Kassite’ and notes: ‘Originally an Old Babylonian seal with two goddesses facing an inscription. The latter was either worn or cut away. Traces of it remain beside the seated figure, which was added, along with the cross and the present inscription, in Kassite times.’ The seal was briefly mentioned in 1996 by Stiehler-Alegria Delgado (1996: 202, no. 194a), and an image of the seal with a modern rollout was presented by Yalcin in 2016 (2016: 134, fig. 7).